In utero exposure to carcinogens: Epigenetics, developmental disruption and consequences in later life. (April 2016) - Waring, R.H.; Harris, R.M.; Mitchell, S.C.
Highlights: The placental "barrier" is permeable to many environmental chemicals. Effects of maternal exposure on the foetus may not appear until it reaches adulthood. Many of these long-term effects are mediated by epigenetic changes. Humans appear to be less sensitive to these effects than common test organisms. Abstract: The uterine environment is often viewed as a relatively safe haven, being guarded by the placenta which acts as a filter, permitting required materials to enter and unwanted products to be removed. However, this defensive barrier is sometimes breached by potential chemical hazards to which the mother may be subjected. Many of these toxins have immediate and recognisable deleterious effects on the embryo, foetus or neonate, but a few are insidious and leave a legacy of health issues that may emerge in later life. Several substances, falling into the categories of metals and metalloids, endocrine disruptors, solvents and other industrial chemicals, have been implicated in the development of long-term health problems in the offspring following maternal and subsequent in utero exposure. The mechanisms involved are complex but often involve epigenetic changes which disrupt normal cell processes leading to the development of cancers and also dysregulation of biochemical pathways.